Approaching Inflammation Paradoxes—Proinflammatory Cytokine Blockages Induce Inflammatory Regulators - Liu, Ming; Saredy, Jason; Zhang, Ruijing; Shao, Ying; Sun, Yu; Yang, William Y.; Wang, Jirong; Liu, Lu; Drummer, Charles; Johnson, Candice; Saaoud, Fatma; Lu, Yifan; et al. (Frontiers in Immunology, 2020)
The mechanisms remain poorly determined that underlie various inflammation paradoxes, metabolically healthy obesity, and increased inflammations after inflammatory cytokine blockades and deficiencies. We performed an extensive –omics database mining, determined the expressions of 1367 innate immune regulators in 18 microarrays after deficiencies of 15 proinflammatory cytokines/regulators and eight microarray datasets of patients receiving Mab therapies, and made a set of significant findings: 1) proinflammatory cytokines/regulators suppress the expressions of innate immune regulators; 2) upregulations of innate immune regulators in the deficiencies of IFN/IFNR1, IL-17A, STAT3 and miR155 are more than that after deficiencies of TNF, IL-1, IL-6, IL-18, STAT1, NF-kB, and miR221; 3) IFN, IFNR and IL-17RA inhibit 10, 59 and 39 proinflammatory cytokine/regulator pathways, respectively; in contrast, TNF, IL-6 and IL-18 each inhibits only four to five pathways; 4) The IFN-promoted and -suppressed innate immune regulators have four shared pathways; IFNR1-promoted and -suppressed innate immune regulators have 11 shared pathways; and miR155-promoted and -suppressed innate immune regulators have 13 shared pathways, suggesting negative-feedback mechanisms in their conserved regulatory pathways for innate immune regulators; 5) Deficiencies of proinflammatory cytokine/regulator-suppressed, promoted programs share signaling pathways and likelihood to develop 11 diseases including cardiovascular disease; 6) There are the shared innate immune regulators and pathways between deficiency of TNF in mice and anti-TNF therapy in clinical patients; 7) Mechanistically, up-regulated reactive oxygen species regulators such as myeloperoxidase caused by suppression of proinflammatory cytokines/regulators can drive the upregulation of suppressed innate immune regulators. Our findings have provided novel insights on various inflammation paradoxes and proinflammatory cytokines regulation of innate immune regulators; and may re-shape new therapeutic strategies for cardiovascular disease and other inflammatory diseases.